2020
DOI: 10.3233/jvr-191059
|View full text |Cite
|
Sign up to set email alerts
|

An analysis of state Pre-Employment Transition Services policies

Abstract: BACKGROUND: In July 2014, the Workforce Innovation and Opportunity Act (WIOA) was signed into law, amending the Rehabilitation Act of 1998 and establishing new workforce initiatives for state vocational rehabilitation (VR) agencies. Final regulations were released in July 2016, requiring state VR agencies to fund and coordinate Pre-Employment Transition Services (Pre-ETS). Many state VR agencies have developed policies to define and address the provision of Pre-ETS in their jurisdictions. Given the recent esta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 16 publications
(26 citation statements)
references
References 8 publications
3
17
0
Order By: Relevance
“…Our study also confirmed previous findings that suggest state plans largely focused on building partnerships to increase employment of youth with disabilities (Carlson et al, 2020; Roux et al, 2019). In fact, not only did these partnerships with various stakeholders expand employment opportunities for individuals with disabilities, but they were often fundamental to the provision of Pre-ETS across states.…”
Section: Discussionsupporting
confidence: 91%
See 4 more Smart Citations
“…Our study also confirmed previous findings that suggest state plans largely focused on building partnerships to increase employment of youth with disabilities (Carlson et al, 2020; Roux et al, 2019). In fact, not only did these partnerships with various stakeholders expand employment opportunities for individuals with disabilities, but they were often fundamental to the provision of Pre-ETS across states.…”
Section: Discussionsupporting
confidence: 91%
“…Findings of this study intersect with and extend the work of previous researchers in examining the impact of WIOA implementation across states (e.g., Carlson et al, 2020; Roux et al, 2019). Previous researchers investigated the extent to which states described Pre-ETS for youth with autism (Roux et al, 2019) and the extent to which state policies addressed Pre-ETS (Carlson et al, 2020). Similarly, we found that the extent to which states described Pre-ETS varied greatly, with some states providing generic statements and others providing in-depth descriptions of services.…”
Section: Discussionsupporting
confidence: 82%
See 3 more Smart Citations